Attitudes and beliefs about HIV/AIDS behaviour and education among Tanzanian youth - Maswanya, E.; Brown, Graham; Merriman, Gareth (CSIRO Publishing, 2009)
Background: Tanzania faced with an increasing problem from HIV sexual infection and vulnerability of students is a key concern. This paper explores beliefs, attitudes and behavioural perspectives on HIV/AIDS education among students in Tanzania as there has been few qualitative information on the subject. Methods: A total of 20 college students of both sexes were interviewed in a qualitative study. Health Belief Model and Social Cognitive Theory were used to guide the interview and constant comparative analysis on their attitudes, beliefs, behaviour and education towards HIV infection risks were utilised. Results: During the interview, the following topics emerged: misinformation and desire for HIV/AIDS education program in school curricula; perceptions of one’s own and peer’s susceptibility to HIV infection; social norms regarding sexual behaviour and perceptions regarding access to education and health services. Lack of accurate information and lack of education at home and at school further contributed to risk behaviour.Conclusion: The study highlighted important perspectives of students towards HIV infection, risk behaviours which are important for HIV prevention programs for students. Based on the findings, recommendations for improvement in prevention programs among college students within Tanzanian schools context are discussed.